Application of Prudential Principles in Registration of Granting Mortgage Right (APHT) - Hesti Kusumaningrum (Authentica, 2019)
The precautionary principle serves as a guideline for PPAT in carrying out the APHT registration process. In-Law No.4 of 1996 concerning Underwriting Rights, PPAT Position, and Civil Regulations No.1 Year 2006 implies the precautionary principle regarding the provision that the PPAT is personally responsible for the duties and authorities in the process of making the deed. PPAT must apply accuracy in registering APHT to the Land Office. Registration becomes an important moment for the birth of Underwriting Right, the fulfillment of the principle of publicity, the position of the preferred creditor as the holder of the Underwriting Right. The data used in this study are secondary data with primary data as secondary data supplementary data. The approach method used in this study is the normative juridical approach. The results of the study obtained concluded that 2 (two) terms of the application of the precautionary principle of the form and content of APHT made by PPAT in accordance with applicable regulations, however, APHT registration occurred later than the 7 (seven) working day deadline. Not applying the precautionary principle can lead to legal consequences for the PPAT, APHT. and preferred creditors, from the aspects of civil, criminal, and administrative law. Preventive and repressive legal protection for all parties concerned in the series of APHT registration processes. Suggestions for PPAT need to apply the precautionary principle to minimize late APHT registration, the Land Office needs to apply administrative sanctions. Keywords: prudential principles; APHT registration; legal consequences